An investigation of Eccentric Versus Concentric Resistance Training: The Role of Movement Velocity and Training Type - Settar Koçak; Gürcan Ünlü (Türk Spor ve Egzersiz Dergisi)
It is known that high intensity dynamic resistance training which involves eccentric and concentric contractions is one of the effective method for maximizing strength. Although, it is postulated that eccentric and concentric contractions provide different physiological adaptations, previous studies comparing the short-term effects of these two contractions have reported contradictory findings, with some studies reporting greater strength development with eccentric, some with concentric and some with similar within both training (18). Methodological differences may be of critical importance to the reported different findings, when focusing on the underlying reasons for these effects are discussed. The majority of previous studies on this topic have used isokinetic equipment to compare eccentric with concentric training, however there are also several studies which used isotonic method which is the most common type of resistance training. Since the effects of these two methods can form different physiological adaptations (9), it may not be proper to review the studies related to eccentric and concentric comparisons without taking into account training method variable. In isokinetic, contraction velocity can be controlled by the dynamometer however it is hard to standardize the movement velocity of isotonic training.  And also previous studies showed that movement velocity of resistance training may affect strength development (11). At this juncture, the aim of this paper was to review the studies investigating eccentric and concentric resistance training and discuss the reported findings by considering methodological differences (training type and movement velocity).  Although it was difficult to present certain implications due to only few studies including same methods in terms of contraction types and training methods, some highlights from this paper can be very informative to further studies. One of them is that the effects of eccentric and concentric resistance training might be different according to training types. The effects of movement velocity of resistance training on strength may also be different in terms of isotonic or isokinetic training methods.